REPRESENTASI KAMPANYE CALON ANGGOTA LEGISLATIF PEREMPUAN PADA PEMILIHAN UMUM TAHUN 2024 - Sophia, Evie; Sutrisno; Hamidah (Linimasa : Jurnal Ilmu Komunikasi, 2024)
Campaigns via social media Instagram are one promising method for achieving this goal. Through this platform, the messages conveyed can be more easily accessed by the wider community, including those who are connected digitally and especially the younger generation who predominantly use social media. This research aims to determine the campaign representation of female legislative candidates posted by the Instagram account @ataliapr @melly_goeslow @ledia_Hanifa. The theory used in this research is Roland Barthes semiontics, the research method used is descriptive qualitative. The results of this research show that the three Instagram accounts represent different campaigns on Instagram social media, the @ataliapr account represents support from her husband and former Governor of West Java to increase popularity. During the campaign, the @melly_goeslow account showed that physical activities such as Zumba exercise were an integral part of life which in turn supported his vision and mission as a member of the legislature. Meanwhile, the @ledia_Hanifa account in the campaign on social media Instagram describes himself as a leader who is committed to the values of social justice